Black Butler: A Neo-Victorian Jack the Ripper and the Child Detective - Joti Bilkhu (Journal of Anime and Manga Studies, 2023)
In Toboso Yana’s anime Black Butler, she pairs the figures of the child detective with Jack the Ripper to arrive at a complex array of meanings. The Ripper figure continues to have one of the most popular afterlives following its original context of Victorian Britain, with numerous contemporary iterations and adaptations of the 1888 murders visible across contemporary popular culture. This article examines the characteristics that Black Butler’s child detective Ciel Phantomhive has in common with the Ripper (tragic histories, violent behavior, and the strategic use of knowledge). I begin by contextualizing Black Butler in regards to Japanese literature, a world literature framework, and the neo-Victorian genre alike. I then turn to analyzing how Ciel deploys the knowledge he gains from the Ripper case to legitimize himself; he both unravels the mystery of this figure and allows it to persist. In essence, the Ripper phenomenon garners such interest precisely because it is a mystery, and Ciel capitalizes on the same uncertainties and (lack of) knowledge as a form of power.